Iron Deficiency: A New Target for Patients With Heart Failure - Rizzo, Caterina; Carbonara, Rosa; Ruggieri, Roberta; Passantino, Andrea; Scrutinio, Domenico (Frontiers in Cardiovascular Medicine, 2021)
Iron deficiency (ID) is one of the most frequent comorbidities in patients with heart failure (HF). ID is estimated to be present in up to 50% of outpatients and is a strong independent predictor of HF outcomes. ID has been shown to reduce quality of life, exercise capacity and survival, in both the presence and absence of anemia. The most recent 2016 guidelines recommend starting replacement treatment at ferritin cutoff values less than 100 mcg/l or between 100 and 299 mcg/l when the transferrin saturation is less than 20%. Beyond its effect on hemoglobin, iron plays an important role in oxygen transport and in the metabolism of cardiac and skeletal muscles. Mitochondria are the most important sites of iron utilization and energy production. These factors clearly have roles in the diminished exercise capacity in HF. Oral iron administration is usually the first route used for iron repletion in patients. However, the data from the IRONOUT HF study do not support the use of oral iron supplementation in patients with HF and a reduced ejection fraction, because this treatment does not affect peak VO2 (the primary endpoint of the study) or increase serum ferritin levels. The FAIR-HF and CONFIRM-HF studies have shown improvements in symptoms, quality of life and functional capacity in patients with stable, symptomatic, iron-deficient HF after the administration of intravenous iron (i.e., FCM). Moreover, they have shown a decreased risk of first hospitalization for worsening of HF, as later confirmed in a subsequent meta-analysis. In addition, the EFFECT-HF study has shown an improvement in peak oxygen consumption at CPET (a parameter generally considered the gold standard of exercise capacity and a predictor of outcome in HF) in patients randomized to receive ferric carboxymaltose. Finally, the AFFIRM AHF trial evaluating the effects of FCM administration on the outcomes of patients hospitalized for acute HF has found significantly fewer hospital readmissions due to HF among patients treated with FCM rather than placebo.